The Successful Rapid Adjustment of Blood Glucose in a Patient With Acute Coronary Syndrome, Renal Insufficiency, and Diabetes: A Case Report of Management Coordinated by Clinical Pharmacists and Clinicians - Shi, Fang-Hong; Shen, Long; Pan, Mang-Mang; Ma, Lin-Lin; Zhang, Chi; Gu, Zhi-Chun; Ma, Jing; Li, Hao (Frontiers in Pharmacology, 2020)
Diabetes is a major cause of cardiovascular mortality in most countries. Intensive management of blood glucose is pivotal for alleviating disease progress and minimizing cardiovascular complications. In this study, we report a case of successful control of high blood glucose in a diabetes patient with acute coronary syndromes (ACS), hypertension, and renal insufficiency. This patient had five years of diabetes history and was hospitalized through an ACS emergency. Coronary angiography showed an acute anterior myocardial infarction (Killip Level Ⅰ). The patient had extremely high blood glucose ranged from 19.4 to 28.2 mmol/L on the first day in the hospital, and experienced significant blood glucosefluctuations in the following three days. After two rounds of clinical pharmacist consultation, the patient’s fasting blood glucose (FBG) target was achieved on the seventh day of his hospitalization and was well controlled afterward. The patient’s postprandial blood glucose (PBG) target was achieved on the ninth day of hospitalization and he was discharged when his blood glucose was well controlled and cardiac function had been fully assessed. Hence, we summarize a protocol that could be used to quickly adjust high blood glucose in hospitalized patients and report a new blood glucose management model coordinated by clinical pharmacists and clinicians.